Divine epiphany in Greek literature and culture - Petridou, Georgia (Oxford scholarship online, 2016)
'Divine Epiphany in Greek Literature and Culture' is the first comprehensive survey of the history of divine epiphany as presented in the literary and epigraphic narratives of the Greek-speaking world